Craniofacial Evolution: From Australopithecus to Modern Man. Issue 1 (January 2022) - Sambataro, Sergio; Fiorillo, Luca; Bocchieri, Salvatore; Stumpo, Chiara; Cervino, Gabriele; Herford, Alan Scott; Cicciù, Marco
Abstract : Abstract: Through the analysis and evaluation of the size and morphology of teeth and jaws, it is possible to differentiate animal species including man, allowing the theory of human evolution to be established. Hominin evolution is characterized by two main features, the transition to bipedality and the increase in brain size. This had an important impact on the structure and function of the hominine skull. The aim of this article is to retrace the evolutionary steps that led to Homo Sapiens, the direct ancestor of modern man. For the following paper, scientific articles from Medline (PubMed) and Google Scholar database were used from 1929 to 2018. Hominid evolution is characterized by 2 main features, the transition to bipedality and the increase in brain size. The fossils found show that both trends have had an important impact on the morphology and function of the skull of modern man. The basicranial flexion and growth have led to the facial modifications typical of modern man. The main changes concern the mandibular evolution with the appearance of the chin, the formation of the Spee curve due to mandibular arch growth, the formation of the temporomandibular joint as a hinge joint with a sliding socket as the condyle and a better function and maximum efficiency than its predecessors thanks to respect for the divine proportions of the face. Knowledge of ontogenesis allows us to know the factors underlying human form and function, analyze and evaluate them in the clinical context. Abstract : Supplemental Digital Content is available in the text